Lgr5‐overexpressing mesenchymal stem cells augment fracture healing through regulation of Wnt/ERK signaling pathways and mitochondrial dynamics. Issue 7 (16th April 2019) - Lin, Weiping; Xu, Liangliang; Pan, Qi; Lin, Sien; Feng, Lu; Wang, Bin; Chen, Shuxun; Li, Ying; Wang, Haixing; Li, Yucong; Wang, Yan; Lee, Wayne Yuk Wai; et al.
ABSTRACT: Fracture remains one of the most common traumatic conditions in orthopedic surgery. The use of mesenchymal stem cells (MSCs) to augment fracture repair is promising. Leucine‐rich repeat‐containing GPCR 5 (Lgr5), a transmembrane protein, has been identified as a novel adult stem cell marker in various organs and tissues. However, the roles of Lgr5 in MSCs are not fully understood. In this study, we investigated cellular functions of Lgr5 in MSCs and its potential implications in treating fracture. Lgr5‐overexpressing MSCs (MSC Lgr5 ) were established in murine SV40 promoter–driven luciferase reporter MSC line through virus transfection. Results of real‐time quantitative PCR and Western blot analysis confirmed the increased expression of Lgr5 in MSC Lgr5 . MSC Lgr5 exhibited increased osteogenic capacity, which may result from elevated expression of β‐catenin and phosphorylated ERK1/2 within the nuclear region of cells. In contrast, inhibition of Lgr5 expression decreased the osteogenic differentiation ability of MSCs, accompanied with increased mitochondrial fragmentation and reduced expression of β‐catenin. Local transplantation of MSC Lgr5 at fracture sites accelerated fracture healing via enhanced osteogenesis and angiogenesis. MSC Lgr5 stimulated the tube formation capacity of HUVECs in a Matrigel coculture system in vitro significantly. Taken together, results suggest that Lgr5 is implicated in the cellular processes of osteogenic differentiation of MSCs through regulation of Wnt and ERK signaling pathways and mitochondrial dynamics in fusion and fission. Inhibition of Lgr5 expression induced increased mitochondrial fragmentation and suppression of osteogenesis. MSC Lgr5 exhibited enhanced therapeutic efficacy for fracture healing, which may serve as a superior cell source for bone tissue repair.—Lin, W., Xu, L., Pan, Q., Lin, S., Feng, L., Wang, B., Chen, S., Li, Y., Wang, H., Li, Y., Wang, Y., Lee, W. Y. W., Sun, D., Li, G. Lgr5‐overexpressing mesenchymal stem cells augment fracture healing through regulation of Wnt/ERK signaling pathways and mitochondrial dynamics. FASEB J. 33, 8565–8577 (2019). www.fasebj.org